Population Pharmacokinetics in Oncology and Its Clinical Applications - Nicolas Widmer; Monia Guidi; Thierry Buclin (MDPI AG, 2024)
Most traditional cytotoxic drugs are characterized by steep dose-response relationships and narrow therapeutic windows [...]